Ferronickel catalytic material, preparation method thereof and application of ferronickel catalytic material in electrolytic hydrogen production test

By using the mixed crystals of nickel oxalate and ferrous acid, combined with the liquid thermal treatment technology of ascorrhea and hydrogen peroxide, nickel -iron catalytic materials with excellent oxidation and reducing performance are prepared, which solves high cost, complex and stable process in existing technologies. Poor sexual problems realize efficient and stable catalytic properties.

CN119332299APending Publication Date: 2025-01-21SICHUAN INST OF PROD QUALITY SUPERVISION INSPECTION & TESTING (SICHUAN QUALITY & TECH REVIEW & EVALUATION CENT) +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411521010.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing electrochemical catalytic materials preparation process has problems such as high cost, cumbersome process, unfriendly environment, and easy falloff between the catalyst and the substrate.

Method used

The hybrid crystals of nickel nickel and ferrous acid metal acid are used as nickel iron catalytic materials. Through liquid thermal treatment technology, weeming of ascorbic acid and hydrogen peroxide use it as a treatment solution to form a stable nickel iron catalyst.

Benefits of technology

It realizes low -cost, high efficiency to prepare nickel -iron catalytic materials with excellent OER performance, and its contact with the base is stable, and it can work stable for a long time under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332299A_ABST
    Figure CN119332299A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical hydrogen production, and provides a ferronickel catalytic material and a preparation method thereof, and an application of the ferronickel catalytic material in an electrolytic hydrogen production test. The ferronickel catalytic material provided by the invention comprises mixed crystals of nickel oxalate and ferrous oxalate, through element distribution diagram analysis of a transmission electron microscope, the atomic ratio of nickel to iron to oxygen to carbon in the nickel-iron catalytic material is (20-30): (10-15): (40-50): (10-15). According to the ferro-nickel catalytic material provided by the invention, the surface micron crystals are tightly combined with the substrate, so that the problems that the catalyst is unstable in structure, easy to fall off and the like in the synthesis process of the OER catalyst are obviously solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical hydrogen production, and in particular, relates to a nickel-iron catalytic material and a preparation method thereof, as well as an application of the nickel-iron catalytic material in electrolytic hydrogen production testing. Background Art

[0002] Global development and population growth have led to an increasing demand for energy, which is expected to reach 23 terawatts by 2030. However, the excessive consumption of fossil fuels has not only accelerated resource depletion, but also caused serious environmental problems. Therefore, the development of renewable and clean alternative energy sources is crucial to the sustainable and green development of human society. To this end, researchers have developed advanced energy conversion processes such as nitrogen fixation, carbon dioxide reduction, and water electrolysis to convert abundant resources in the atmosphere into high-value chemicals through electrocatalysis. In recent years, energy-related electrocatalytic processes have focused on three main cycles: the nitrogen cycle, the carbon cycle, and the water cycle.

[0003] Electrocatalytic nitrogen cycling is a hot topic in research, involving nitrogen reduction oxidation reactions (NRR and NOR), NO x Reduction and ammonia oxidation processes. In order to reduce the kinetic barriers of these reactions and increase the reaction rates, highly active electrocatalysts are required. In the carbon cycle, the carbon dioxide reduction reaction (CRR) is the main electrocatalytic reaction, which has a high kinetic barrier and the control of the reaction pathway is extremely challenging. The water cycle includes several electrocatalytic reactions related to hydrogen and oxygen, such as the decomposition of water into hydrogen and oxygen through the hydrogen evolution reaction and oxygen evolution reaction (HER and OER), and the hydrogen oxidation reaction and oxygen reduction reaction (HOR and ORR) occurring at the anode and cathode of the electrocatalytic cell. Typically, OER is the bottleneck in these reactions that affects energy efficiency and commercialization.

[0004] Currently, noble metal-based electrocatalysts (such as platinum catalysts for HER and ORR, ruthenium catalysts for OER, and gold catalysts for CRR) exhibit high electrocatalytic efficiency. However, the high cost, limited resources, and poor durability of noble metals limit their widespread application and hinder the large-scale commercialization of energy technologies. In contrast, efficient non-noble metal OER catalysts have attracted much attention due to their high intrinsic activity, electrolysis durability, long-term chemical-mechanical stability, and adaptability to large-scale applications. Therefore, the development of efficient, robust, and low-cost OER catalysts has become a key task for the production of renewable fuels.

[0005] Among the many non-precious metal OER catalysts, nickel-iron compounds show the best electrocatalytic activity under alkaline conditions. Studies have shown that the presence of Fe can enhance the electrocatalytic activity of Ni 3+oxidation ability. In addition to optimizing the intrinsic activity by adjusting the material composition, it is equally important to enhance the high activity of the nickel-iron substrate (NiFe substrate). Currently, there are two common strategies: one is to reduce the diameter of the substrate particles or increase the layering to expand the electrochemical surface area, thereby exposing more active sites; the other is to integrate the NiFe substrate with a conductive material to promote efficient charge transfer and reaction kinetics. In the latter strategy, the enhanced electron transfer efficiency and the strong interaction between the active phase and the substrate can change the local electronic structure of the metal center, thereby improving the redox performance and being more conducive to the OER reaction.

[0006] The study also found that the aggregation of transition metal ions will reduce the electrochemically active surface area (ECSA) and interfacial free energy, which is not conducive to the activity of the catalyst. Therefore, it is very important to reduce the agglomeration of metal particles. Summary of the invention

[0007] Technical problems solved by the present invention:

[0008] It is used to solve the problems of high cost, complicated process flow, environmental unfriendliness, and easy detachment of catalyst from substrate (i.e. poor stability) in the existing preparation process of electrochemical catalytic materials.

[0009] The technical solution adopted by the present invention is:

[0010] First, the present invention provides a nickel-iron catalytic material, which comprises mixed crystals of nickel oxalate and ferrous oxalate.

[0011] The mixed crystals contain nickel oxalate and ferrous oxalate, which are usually regular in shape, such as cuboids, needles or sheets. When in a cuboid shape, the mixed crystals are deposited on the surface of the metal substrate in a parallel or staggered manner. This shape is conducive to the formation of an orderly layered stack of mixed crystals on the surface of the substrate. Thereby affecting the contact mode between the crystals and the substrate, thereby affecting their adhesion and stacking stability. In an embodiment of the present invention, it is presented in a cuboid shape. When in a cuboid shape, the size of the cuboid is an average of 1.0 to 5.0 μm in length × 0.5 to 2.3 μm in width × 0.5 to 2.6 μm in height.

[0012] In addition to the various morphologies of the mixed crystals mentioned above, the non-covalent bonding between the mixed crystals and the metal substrate can also promote the mixed crystals to deposit on the surface of the metal substrate and form a stable stacking structure. The non-covalent bonding here includes van der Waals forces and / or electrostatic forces.

[0013] In the above, the nickel-iron catalytic material includes a mixed crystal of nickel oxalate and ferrous oxalate, which is obtained through the following test determination.

[0014] First, the ratio of each element in the nickel-iron catalytic material is determined by TEM-mappling characterization, and the specific measurement results are: the atomic ratio of nickel, iron, oxygen, and carbon is 20-30:10-15:40-50:10-15. Previously, the applicant used TEM-mappling characterization and SEM-mappling characterization at the same time. TEM-mappling characterization was finally used as the standard because: during the SEM test, the sample was mounted on a commercial nickel-iron substrate, and the SEM component analysis was a micro-area detection of a specific area on the surface of the sample, so there may be certain errors. This error mainly stems from the interference of the substrate on the signal and the complexity of the surface level, so that the measured element ratio may not fully represent the actual composition of the sample. In contrast, the TEM test uses a processed sample and mounts it on a copper mesh for detection. The use of a copper mesh reduces interference with elemental analysis, making the results more reliable and accurate. Therefore, TEM is selected, which can provide higher resolution and more detailed element distribution information, so its results are generally considered to be more representative.

[0015] Secondly, the nickel-iron catalyst material is a mixed crystal of nickel oxalate and ferrous oxalate, which is determined by the X-ray diffraction (XRD) diffraction peak. That is: the XRD diffraction peak of the nickel-iron catalyst material is the same as that of NiC 2 O 4 ·2H 2 O (PDF#00-025-0581) and C 2 Fe 2+ O 4 ·2H 2 O(PDF#00-023-0293) matches well. Most of the diffraction peaks are attributed to NiC 2 O 4 ·2H 2 O.

[0016] Second, the present invention provides a method for preparing the aforementioned nickel-iron catalytic material, comprising the following steps:

[0017] The metal substrate is heat treated with a treatment solution including ascorbic acid and hydrogen peroxide to obtain a nickel-iron catalytic material.

[0018] According to some preferred embodiments, the metal substrate is a nickel-iron foam substrate (NFF).

[0019] According to some preferred embodiments, the concentration of hydrogen peroxide in the treatment solution is 2-3 wt %.

[0020] According to some preferred embodiments, in the treatment solution, the addition ratio of ascorbic acid to hydrogen peroxide is 0.02-0.16 mol / L:1L, specifically, 0.02 mol / L:1L, 0.04 mol / L:1L, 0.06 mol / L:1L, 0.08 mol / L:1L, 0.10 mol / L:1L, 0.12 mol / L:1L, 0.14 mol / L:1L, 0.16 mol / L:1L, and ranges between the aforementioned values. Further, preferably, 0.08-0.12 mol / L:1L; further, preferably, 0.1 mol / L:1L.

[0021] According to some preferred embodiments, the heat treatment is carried out at 80-120° C. for 0.5-2 h.

[0022] According to some more preferred embodiments, the heat treatment is carried out at 100° C. for 1 hour.

[0023] In the present invention, a strong oxidant (hydrogen peroxide) and a reducing agent (ascorbic acid) are used to act on a metal substrate through heat treatment technology, so that a crystalline solid (mixed crystal) is attached to the surface of the metal substrate, thereby preparing an OER nickel-iron catalyst.

[0024] In the above, the reasons for selecting hydrogen peroxide and ascorbic acid are as follows:

[0025] First, ascorbic acid can effectively complex with metal ions, reduce particle agglomeration, and further accelerate the formation of holes and defects by corroding the surface of metal materials, providing more active sites for OER reactions.

[0026] Second, hydrogen peroxide (H 2 O 2 ) As an important green chemical, it not only has high calorific value and environmentally friendly properties, but also acts as a strong oxidant, producing only water and oxygen as byproducts. The active substances such as oxygen free radicals produced by the decomposition of hydrogen peroxide can oxidatively etch the surface of the nickel-iron substrate, remove impurities and pollutants on the surface, or modify the surface to a certain extent, increasing the surface roughness or active sites. The strong oxidizing ability of hydrogen peroxide can react with metal electrons to produce free radicals, significantly enhancing the corrosion effect on the metal substrate.

[0027] Third, the mechanism of ascorbic acid and hydrogen peroxide acting on metal substrates:

[0028] (1) Ascorbic acid generates small molecular organic acids (such as oxalic acid, formic acid, acetic acid, etc.) under heat treatment and the action of hydrogen peroxide. At higher temperatures (such as 100°C), ascorbic acid easily decomposes to produce oxalic acid.

[0029] Ascorbic acid (C 6 H8 O 6 )→oxalic acid (H 2 C 2 O 4 )+other by-products

[0030] (2) With the participation of hydrogen peroxide, the metal substrate (nickel-iron substrate) is oxidized to Ni 2+ and Fe 2+ .

[0031] Ni→Ni 2 ++2e-

[0032] Fe→Fe2++2e-

[0033] (3) Oxalate combines with metal ions to form a precipitate. That is, the oxalate ion (C 2 O 4 2- ) combines with nickel and iron metal ions in solution to form nickel oxalate (NiC 2 O 4 ) precipitation and ferrous oxalate (C 2 Fe 2+ O 4 ) precipitation. Subsequently, nickel oxalate precipitate and ferrous oxalate precipitate gradually precipitate out of the solution and deposit on the surface of the metal substrate to form crystals.

[0034] Ni 2+ +C 2 O 4 2- →NiC 2 O 4

[0035] Fe 2+ +C 2 O 4 2- →C 2 Fe 2+ O 4

[0036] Fourthly, in addition to the reducing agent mentioned above, ascorbic acid also has the following effects:

[0037] (1) Ascorbic acid decomposes to form oxalate, which, under heating and oxidation conditions, decomposes to form oxalate, thereby forming nickel oxalate and ferrous oxalate.

[0038] (2) Ascorbic acid can also provide mild reducing conditions, which can promote the dissolution and ionization of nickel and iron without destroying the nickel-iron matrix structure. Other reducing agents cannot maintain this stability under the same temperature and environment, or will cause side reactions.

[0039] (3) Ascorbic acid has the advantages of low toxicity and low environmental harm, while other reducing agents may bring additional pollution or safety issues.

[0040] Fifth, hydrogen peroxide has the following effects:

[0041] (1) Hydrogen peroxide has a controllable oxidizing effect. Specifically, hydrogen peroxide decomposes into water and oxygen under heating conditions, providing a mild and controllable oxidizing environment. This oxidizing environment is critical for promoting metal dissolution and the decomposition reaction of ascorbic acid. Other strong oxidants may cause excessive oxidation or the formation of by-products, thereby interfering with the formation of crystals (i.e., crystallization).

[0042] (2) The synergistic effect of hydrogen peroxide and ascorbic acid: hydrogen peroxide can ensure that ascorbic acid will not decompose and become ineffective quickly under oxidative conditions, thereby ensuring the continued progress of the reaction. Other oxidants may not have this mild synergy, which will lead to an unbalanced reaction process.

[0043] Third, the present invention provides an application of the nickel-iron catalytic material as described above in a hydrogen production electrolysis test.

[0044] Fourth, the present invention provides an application method of the nickel-iron catalytic material mentioned above in the electrolytic hydrogen production test, using 1 mol / L potassium hydroxide as the electrolyte, using a standard three-electrode configuration, using the nickel-iron catalytic material as the anode, mercury / mercuric oxide as the reference electrode, and a platinum plate as the counter electrode, and testing its OER performance by cyclic voltammetry (CV method) [voltage window is 0-1V (V vs.Hg / HgO)]. Specifically, the electrode is scanned by cyclic voltammetry for 1 to 5 cycles at a voltage window of 0 to 1V.

[0045] The nickel-iron catalytic material provided by the present invention has the following advantages:

[0046] (1) The nickel-iron catalytic material provided by the present invention has a distinct three-dimensional block structure, provides abundant reaction active sites, has excellent electrical conductivity, and strong interface bonding force, providing excellent and stable OER performance.

[0047] (2) Taking the mixed solution of (0.1 mol / L ascorbic acid + hydrogen peroxide) as an example to treat the nickel-iron substrate at 100°C and perform CV activation treatment at room temperature, the -2 , 50mA cm -2 and 150mA cm -2At current densities of 1000 Å and 2000 Å, the overpotentials were 120 mV, 140 mV, and 207 mV, respectively, which were better than those obtained by thermochemical treatment of pure ascorbic acid (265 mV, 312 mV, and 335 mV) and that obtained by thermochemical treatment of pure hydrogen peroxide (310 mV, 362 mV, and 395 mV). In the constant voltage polarization test, the nickel-iron catalytic material was able to -2 It can work stably for at least 800 hours under industrial-grade current density without obvious performance degradation. The above data all reflect that the OER performance of the nickel-iron catalytic material provided by the present invention is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 LSV curve of HVc@NFF at different HVc concentrations;

[0049] Figure 2 It is the LSV test diagram of each test sample;

[0050] Figure 3 is the overpotential diagram of oxygen evolution reaction of each test sample;

[0051] Figure 4 This is the HVc@NFF stability test diagram;

[0052] Figure 5 It is the EIS comparison diagram of each test sample at a specific DC potential;

[0053] Figure 6 It is a comparison chart of TOF values ​​of each test sample;

[0054] Figure 7 This is the SEM image of HVc@NFF;

[0055] Figure 8 SEM image of Vc@NFF;

[0056] Fig. 9 is the SEM image of H@NFF;

[0057] Fig.10 is the element distribution diagram of HVc@NFF;

[0058] Fig.11 TEM and SEM element content determination results of HVc@NFF;

[0059] Fig.12 This is the XRD diffraction pattern of HVc@NFF. DETAILED DESCRIPTION

[0060] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0061] Example 1

[0062] The present embodiment provides a nickel-iron catalytic material, and the preparation method includes the following steps: dissolving ascorbic acid (white powder medicine) in a 3wt% hydrogen peroxide aqueous solution to obtain a pretreatment solution, placing commercial nickel-iron foam (NFF) (Suzhou Zhengtai Rong New Materials Co., Ltd.), and placing the nickel-iron substrate in a mixed solution of hydrogen peroxide and ascorbic acid, heating it in an environment of 100°C for 1h, removing the commercial nickel-iron foam after heat treatment, rinsing it with deionized water, and placing it in a 40°C oven for drying. The sample is marked as HVc@NFF (wherein H represents hydrogen peroxide, Vc represents ascorbic acid, and NFF represents a commercial nickel-iron foam substrate). The ratio of each specific parameter in Example 1 is shown in Table 1.

[0063] Table 1 Detailed list of experimental parameters

[0064]

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 1 is that commercial nickel-iron foam is treated with an aqueous solution having a concentration of 0.1 mol / L of ascorbic acid, and after heating in an environment of 100°C for 1 hour, the metal substrate is rinsed with deionized water and placed in an oven at 40°C for drying. The sample is marked as Vc@NFF (Vc represents ascorbic acid, and NFF represents a commercial nickel-iron foam substrate). The ratio of each specific parameter in Comparative Example 1 is shown in Table 2.

[0067] Table 2 Detailed list of experimental parameters

[0068]

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that commercial nickel-iron foam is treated with only an aqueous solution with a hydrogen peroxide concentration of 3wt%, and after heating in an environment of 100°C for 1h, the metal substrate is rinsed with deionized water and placed in an oven at 40°C for drying. The sample is marked as H@NFF (H represents hydrogen peroxide, and NFF represents a commercial nickel-iron foam substrate). The ratio of each specific parameter in Comparative Example 2 is shown in Table 3.

[0071] Table 3 Detailed list of experimental parameters

[0072]

[0073] Comparative Example 3

[0074] The difference between this comparative example and Example 1 is that no treatment is performed on the commercial nickel-iron foam substrate (NFF), which is marked as NFF. The proportions of the specific parameters in Comparative Example 3 are shown in Table 4.

[0075] Table 4 Detailed list of experimental parameters

[0076]

[0077] Test example

[0078] 1.CV, LSV, TOF and EIS tests

[0079] Taking the HVc@NFF catalytic material in Example 1 as an example, a performance test was performed.

[0080] The test process is as follows: In 1 mol / L KOH, a standard three-electrode system is used, the counter electrode is a platinum sheet (10mm*10mm*0.1mm), Hg / HgO is used as the reference electrode, and the commercial nickel-iron foam substrate treated with ascorbic acid and hydrogen peroxide is used as the working electrode. At room temperature, the electrochemical detection is performed using the Wuhan Coster electrochemical workstation, and the TOF value is calculated after electrochemical testing in a PBS solution with a pH of 7.

[0081] Table 5 is the measurement results of Example 1 and Comparative Examples 1-3.

[0082] Table 5 Oxygen evolution overpotential test table

[0083]

[0084] The results show that the nickel-iron substrate treated with ascorbic acid and hydrogen peroxide exhibits excellent OER catalytic performance, and the optimal synthesis conditions are ascorbic acid 3wt% hydrogen peroxide solution with a ratio of 0.1mol / L. The material achieves its best performance after a reaction time of 1h and a temperature of 100°C.

[0085] Figure 1 Figure 3 is the LSV curve of HVc@NFF samples after treatment with different ascorbic acid concentrations and hydrogen peroxide ratios. It can be clearly observed that when the addition ratio of ascorbic acid to hydrogen peroxide is 0.1 mol / L, the catalyst exhibits the best performance.

[0086] Specifically: Figure 1The concentrations of ascorbic acid in each sample were 0.02mol / L, 0.04mol / L, 0.06mol / L, 0.08mol / L, 0.10mol / L, 0.12mol / L, 0.14mol / L, and 0.16mol / L, respectively; the amount of hydrogen peroxide added was the same. That is, 0.002 to 0.016mol of ascorbic acid was added to 100mL of hydrogen peroxide solution. Figure 1 The LSV curve of the measured sample takes the above reaction conditions (the ratio of ascorbic acid to 3 wt % hydrogen peroxide solution is 0.10 mol / L, the reaction time is 1 h, and the temperature is 100° C.) as the optimal treatment conditions, taking into account the reaction effect and cost consumption.

[0087] Figure 2 is the LSV curve of each sample. Figure 2 It was found that the initial overpotential of HVc@NFF was lower than that of comparative examples 1-3, and it had good OER performance.

[0088] Figure 3 The overpotential comparison of each sample is shown in Figure 2. As the current density increases, the overpotential of each sample also increases. However, the overpotential of HVc@NFF is always lower than that of other samples at the same current density. Even at a current density of 150 mA cm -2 The overpotential is only 231mV, which is lower than NFF at 10mA cm -2 The overpotential (355mV) is below.

[0089] Figure 4 is the constant potential polarization curve of HVc@NFF in 1 mol / L KOH solution. Figure 4 It can be concluded that at 1Acm -2 At the current density, HVc@NFF can run stably for 800 hours with stable performance, which also shows that even at industrial current density, HVc@NFF still has excellent structural stability and OER cycle stability.

[0090] Figure 5 The electrochemical impedance spectroscopy (EIS) comparison diagram of each sample at a DC potential of 0.53V (relative to Hg / HgO) shows that HVc@NFF has the smallest semicircle diameter, the lowest charge transfer resistance and the lowest diffusion resistance compared with other samples. This phenomenon indicates that under the combined action of hydrogen peroxide and ascorbic acid, the diffusion resistance of the nickel-iron substrate is reduced and the electron transfer rate of the nickel-iron substrate is accelerated. The excellent charge transfer ability of HVc@NFF is the key factor for its excellent OER activity.

[0091] Figure 6The turnover frequency (TOF) value comparison chart of each sample. At 0.48V voltage (relative to RHE), the TOF value of HVc@NFF is 1.7s -1 , is Vc@NFF(0.12s -1 ) is 14 times that of H@NFF(0.03s -1 ). TOF results demonstrated that HVc@NFF has higher intrinsic OER activity.

[0092] 2. Microstructure and chemical properties

[0093] Taking HVc@NFF in Example 1 as an example, its microstructure and chemical properties are analyzed. The specific results are shown in Figure 7-Figure 12 .

[0094] Figure 7 This is a SEM image of a commercial metal substrate (nickel-iron foam) after being treated with ascorbic acid and hydrogen peroxide. Figure 7 It can be seen that the passivation film on the treated substrate surface is completely destroyed, forming a dense crystalline layer.

[0095] Figure 8 and Fig. 9 SEM images of Vc@NFF and H@NFF, respectively. Figure 7 It can be clearly seen that after only treatment with ascorbic acid or only treatment with hydrogen peroxide, the skeleton surface of the commercial metal substrate (nickel-iron foam) still presents a smooth appearance without obvious damage trend, which further highlights the good effect of the synergistic effect of ascorbic acid and hydrogen peroxide on the nickel-iron foam substrate.

[0096] Fig.10 This is the element distribution map of HVc@NFF. The image shows that O, C, Fe, and Ni elements are evenly distributed in the micron-crystalline layer, proving that the sample has undergone sufficient reaction and generated stable compounds.

[0097] Fig.11 The TEM and SEM test results of HVc@NFF are shown in Figure 2. Fig.11As shown in the figure, the SEM mapping results show that the atomic ratios of nickel (Ni), iron (Fe), oxygen (O) and carbon (C) in the sample are 3.47:2.92:62.95:30.67, respectively. However, through TEM mapping analysis, we obtained different results, in which the atomic ratios of Ni, Fe, O and C were 27.98:13.33:47.19:11.5, respectively. This difference may be caused by several factors. First, during the SEM test, the sample was mounted on a commercial nickel-iron substrate, and the composition analysis of SEM is a micro-area detection of a specific area on the surface of the sample, so there may be a certain error. This error mainly comes from the interference of the substrate on the signal and the complexity of the surface layer, so the measured element ratio may not fully represent the actual composition of the sample. In contrast, the TEM test uses a processed sample and mounts it on a copper grid for detection. The use of a copper grid reduces interference with elemental analysis, making the results more reliable and accurate. TEM can provide higher resolution and more detailed element distribution information, so its results are generally considered to be more representative. Combining the analysis results of SEM and TEM, it can be inferred that the actual atomic ratio of nickel, iron, oxygen and carbon in the HVc@NFF sample is approximately 27.98:13.33:47.19:11.5.

[0098] Fig.12 is the XRD diffraction pattern of HVc@NFF. Fig.12 As shown, the XRD diffraction peaks of HVc@NFF sample are similar to those of NiC 2 O 4 ·2H 2 O (PDF#00-025-0581) and C2Fe 2+ O 4 ·2H 2 O(PDF#00-023-0293) matches well. Most of the diffraction peaks are attributed to NiC 2 O 4 ·2H 2 O.

[0099] The above analysis shows that the micron-crystalline nickel-iron catalytic material provided by the present invention can quickly corrode the surface of a commercial metal substrate (nickel-iron foam) to form a unique crystalline structure, and exhibits excellent OER performance.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nickel-iron catalytic material, characterized in that: The nickel-iron catalytic material comprises mixed crystals of nickel oxalate and ferrous oxalate; according to the element distribution analysis by transmission electron microscopy, the atomic ratios of nickel, iron, oxygen and carbon in the nickel-iron catalytic material are 20-30:10-15:40-50:10-15.

2. The nickel-iron catalytic material according to claim 1, characterized in that The mixed crystal includes at least one of features (A1) to (A4): (A1) the mixed crystals are in at least one of the following shapes: cuboid, needle, or flake; (A2) The mixed crystals are in the shape of a cuboid; the average size of the cuboid is 1.0-5.0 μm in length × 0.5-2.3 μm in width × 0.5-2.6 μm in height; (A3) The mixed crystals are deposited on the surface of the metal substrate in a parallel or staggered manner; (A4) The mixed crystals are deposited on the surface of the metal substrate through non-covalent bonding.

3. A method for preparing the nickel-iron catalytic material as claimed in claim 1 or 2, characterized in that: The steps include: The metal substrate is heat treated with a treatment solution including ascorbic acid and hydrogen peroxide to obtain a nickel-iron catalytic material.

4. The method for preparing the nickel-iron catalytic material according to any one of claim 3, characterized in that: The addition ratio of ascorbic acid to hydrogen peroxide is 0.02-0.16 mol / L:1L; the concentration of hydrogen peroxide is 2-3 wt%.

5. The method for preparing the nickel-iron catalytic material according to claim 4, characterized in that: The addition ratio of ascorbic acid to hydrogen peroxide is 0.08-0.12 mol / L:1L; the concentration of hydrogen peroxide is 2-3 wt%.

6. The method for preparing the nickel-iron catalytic material according to claim 5, characterized in that: The addition ratio of ascorbic acid to hydrogen peroxide was 0.10 mol / L:1 L; the concentration of hydrogen peroxide was 3 wt %.

7. The method for preparing the nickel-iron catalytic material according to any one of claims 3 to 6, characterized in that: Heat treatment: 80-120℃ for 0.5-2h.

8. The method for preparing the nickel-iron catalytic material according to claim 7, characterized in that: Heat treatment: 100℃ for 1h.

9. Application of the nickel-iron catalytic material as claimed in claim 1 or 2, or the nickel-iron catalytic material obtained by the preparation method as claimed in any one of claims 3 to 8 in a hydrogen production test by electrolysis.

10. A method for using the nickel-iron catalytic material as claimed in claim 9 in a hydrogen electrolysis test, characterized in that: The oxygen evolution reaction performance was tested by cyclic voltammetry using potassium hydroxide as the electrolyte and a standard three-electrode configuration, with nickel-iron catalytic material as the anode, mercury / mercuric oxide as the reference electrode, and a platinum plate as the counter electrode.